PEMBERDAYAAN UMKM MAKANAN LOKAL MELALUI INOVASI PRODUK DAN STRATEGI DIGITALISASI UNTUK MENINGKATKAN DAYA SAING PASAR DI KABUPATEN SEMARANG - Novandalina, Arini; Ernawati, Fidyah (BESIRU : Jurnal Pengabdian Masyarakat, 2024)
This community service project aims to empower local food Micro, Small, and Medium Enterprises (UMKM) in Semarang Regency through product innovation and digitalization strategies to enhance their market competitiveness. The project addresses the issue of low market competitiveness of local food UMKM, which hinders their growth and development. The project employs a participatory approach, involving training and mentoring for UMKM owners, to develop innovative products and digital marketing strategies. The results show a significant improvement in the quality and competitiveness of local food products, as well as an increase in online sales and customer engagement. This project contributes to the empowerment of local food UMKM, promoting local economic growth and community development in Semarang Regency.